Stent-Apposition Salvage of an Anterior Tibial Artery After Inadvertent Angioplasty Balloon Retention During CTO Revascularization - R. Choudry (EJVES Short Reports, 2016)
Introduction: Progressive improvement in the ability to treat complete total occlusions in the tibial level arterial circulation have made it possible to revascularize patients with critical limb ischemia. Report: A 59 year old male presented with a complete total occlusion of his anterior tibial artery with distal reconstitution through peroneal artery collaterals. During attempted angioplasty a balloon was retained within the patent portion of the target vessel. Two 3.0 mm drug eluting coronary stents were deployed across the length of the balloon with excellent luminal preservation. Discussion: Successful CTO revascularization was completed and a strong dorsalis pedis artery pulse was restored following intervention. Keywords: Revascularization, Stent, CTO, Endovascular, Complications